INCIDENCE OF MICRO DETACHMENTS AFTER SUCCESSFUL SCLERAL BUKLING SURGERY FOR MACULA - OFF RETINAL DETACHMENTS - Saeed, Abdullah Naeem; Batool, Isra; Masud, Haleema; Qureshi, Nadeem (Pakistan Armed Forces Medical Journal, 2020)
Objective: To determine the incidence of micro detachments and change in mean height of persistent sub-retinal fluid (SRF) in eyes that underwent successful scleral buckling surgery for macula-off rhegmatogenous retinal detachment (RRD).Study Design: Prospective cohort study. Place and Duration of Study: Retina Department, Al Shifa Trust Eye Hospital Rawalpindi, from Jan 2016 to Dec 2016.Methodology: Thirty two patients that underwent successful scleral buckling surgery for macula-off RD were included in the study. Pre-operative assessment including retinal examination by slit-lamp bio microscopy was carried out before surgery. Post-operative assessment included best corrected visual acuity (BCVA) with a Snellen chart and optical coherence tomography (OCT) by OCT Spectralis, Heidelberg Engineering. The post-operative assessment was performed at 1 week, 1 month, 3 months and 6 months after surgery. Results: The incidence of micro detachments was 31.25% (10 patients) as detected by presence of sub-retinal fluid on optical coherence tomography at one week postoperative and 9.38% (3 patients) at six months after surgery while the base population was considered to be 32. The mean height of persistent sub-retinal fluid decreased significantly at all 4 time-points after the surgery. Mean height of SRF at 1 week, 1 month, 3 months and 6 months after surgery was 357.42 ± 114.25μm, 303.67 ± 107.57μm, 267.36 ± 106.79μm and 240.45 ± 19.77μm respectively.Conclusion: Incidence of micro detachments decreased significantly after scleral buckling surgery up to a period of 6 months with only a small fraction of patients having persistent sub-retinal fluid after 6 months of surgery.